2014
DOI: 10.1002/hed.23722
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying fibrosis in head and neck cancer treatment: An overview

Abstract: Quantitative assessment of neck fibrosis is sought after in order to compare treatment regimens and improve quality of life outcomes in patients with head and neck cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 69 publications
0
33
0
5
Order By: Relevance
“…Radiation therapy-induced fibrosis is associated with expression of inflammatory cytokines (transforming growth factor [TGF]-b), which stimulate fibroblast proliferation, differentiation into fibrocytes, and collagen production. Fibrosis due to radiation therapy is a dynamic process with an apparently uncontrolled remodeling phase and increased severity over time (49,50). The extent of radiation therapyinduced fibrosis and organ atrophy may differ from one patient to another, even if identical radiation therapy treatments are used (50), and it has been suggested that genetic factors, additional chemotherapy, corticosteroid administration, and fractionation schedule may contribute to variability in individual radiosensitivity (51).…”
Section: Key Findings At Mr Dw and Pet/mr Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiation therapy-induced fibrosis is associated with expression of inflammatory cytokines (transforming growth factor [TGF]-b), which stimulate fibroblast proliferation, differentiation into fibrocytes, and collagen production. Fibrosis due to radiation therapy is a dynamic process with an apparently uncontrolled remodeling phase and increased severity over time (49,50). The extent of radiation therapyinduced fibrosis and organ atrophy may differ from one patient to another, even if identical radiation therapy treatments are used (50), and it has been suggested that genetic factors, additional chemotherapy, corticosteroid administration, and fractionation schedule may contribute to variability in individual radiosensitivity (51).…”
Section: Key Findings At Mr Dw and Pet/mr Imagingmentioning
confidence: 99%
“…Fibrosis due to radiation therapy is a dynamic process with an apparently uncontrolled remodeling phase and increased severity over time (49,50). The extent of radiation therapyinduced fibrosis and organ atrophy may differ from one patient to another, even if identical radiation therapy treatments are used (50), and it has been suggested that genetic factors, additional chemotherapy, corticosteroid administration, and fractionation schedule may contribute to variability in individual radiosensitivity (51). Combined treatment modalities (ie, radiation therapy with surgery or chemotherapy) can further lead to increased severity of fibrosis (51,52).…”
Section: Key Findings At Mr Dw and Pet/mr Imagingmentioning
confidence: 99%
“…For HNC, MRE might provide an alternative or complementary option for tumor differentiation and treatment response evaluation. For instance, fibrosis is a common late complication of radiotherapy for HNCs and is difficult to quantify, MRE might be used for this purpose (108). A customized external driver suitable for MRE of the head and neck has been proposed and preliminarily tested on six healthy volunteers and three patients with HNC (109).…”
Section: Mr Elastography (Mre)mentioning
confidence: 99%
“…2 This can be problematic for patients 3 and may additionally impede clinical examination during follow up. 4,5 Neck ultrasound may be useful to evaluate nodal status in these patients. 6,7 Wood is a natural composite of cellulose fibers, which are strong in tension, embedded in a matrix of lignin which resists compression.…”
Section: Introductionmentioning
confidence: 98%